WAHHABISM IN TERMS OF ITS EFFECTS (SAMPLE OF THE COUNTRIES OTHER THAN SAUDI ARABIA) - Rifat TÜRKEL (Fırat University, 2019)
Emerged in the region of Necd in Saudi Arabia during the 18th century, Wahhabism turned out to be a sectarian movement influencing the entire Saudi Arabia and not just remained a cult limited to a region only thanks to the effects of the predominant religious, geographical, political and socio-cultural backgrounds. In addition to the elements listed above, Personal characteristics of Muhammed b. Abdilvehhâb-the leader of Wahhabism- also appear as important factors helping spread of Wahhabism during its early years. It is striking that this sectarian movement gained significant number of followers in various regions of the world while it was initially adopted only in the Arabian Peninsula. It is observed that various sectarian movements emerged among Muslims in Africa and in Indian Subcontinent due to the fact that the European countries set their eyes on and eventually invaded these regions during the 18th and 19th centuries. Muslims inhabitants thereof resorted to develop a variety of methods to overcome political, social as well as religious crises in which they find themselves. As a result of such methods, different sectarian movements and religious trends came out, and thus an affinity has been established between many of such sectarian movements and Wahhabism. It is asserted that Wahhabism was not only influential in Saudi Arabia but also on many religious organizations and sectarian movements that came out in Africa, Central Asia and other regions of the world. It requires further research to determine whether such sectarian movements and trends having similar opinions to Wahhabism were actually influenced by it or not, and if that is true then their degree of exposure should be examined as well. Whether Wahhabism actually influenced any sectarian movements appeared in various geographical regions, and if there really exists such influence, then what their degree of exposure was, and what specific proselyting methods Wahhabis did utilize to spread their opinions and views were the questions we aimed to answer in this study.